Accumulation of Iron Oxide-Based Contrast Agents in Rabbit Atherosclerotic Plaques in Relation to Plaque Age and Vulnerability Features - Sekita, Alexander; Unterweger, Harald; Berg, Sonja; Ohlmeyer, Sabine; Bäuerle, Tobias; Zheng, Kang H.; Coolen, Bram F.; Nederveen, Aart J.; Cabella, Claudia; Rossi, Silvia; Stroes, Erik S.G.; Alexiou, Christoph; et al. (International Journal of Nanomedicine, 2024)
Purpose: In this study, a detailed characterization of a rabbit model of atherosclerosis was performed to assess the optimal time frame for evaluating plaque vulnerability using superparamagnetic iron oxide nanoparticle (SPION)-enhanced magnetic resonance imaging (MRI). Methods: The progression of atherosclerosis induced by ballooning and a high-cholesterol diet was monitored using angiography, and the resulting plaques were characterized using immunohistochemistry and histology. Morphometric analyses were performed to evaluate plaque size and vulnerability features. The accumulation of SPIONs (novel dextran-coated SPIONDex and ferumoxytol) in atherosclerotic plaques was investigated by histology and MRI and correlated with plaque age and vulnerability. Toxicity of SPIONDex was evaluated in rats. Results: Weak positive correlations were detected between plaque age and intima thickness, and total macrophage load. A strong negative correlation was observed between the minimum fibrous cap thickness and plaque age as well as the mean macrophage load. The accumulation of SPION in the atherosclerotic plaques was detected by MRI 24 h after administration and was subsequently confirmed by Prussian blue staining of histological specimens. Positive correlations between Prussian blue signal in atherosclerotic plaques, plaque age, and macrophage load were detected. Very little iron was observed in the histological sections of the heart and kidney, whereas strong staining of SPIONDex and ferumoxytol was detected in the spleen and liver. In contrast to ferumoxytol, SPIONDex administration in rabbits was well tolerated without inducing hypersensitivity. The maximum tolerated dose in rat model was higher than 100 mg Fe/kg. Conclusion: Older atherosclerotic plaques with vulnerable features in rabbits are a useful tool for investigating iron oxide-based contrast agents for MRI. Based on the experimental data, SPIONDex particles constitute a promising candidate for further clinical translation as a safe formulation that offers the possibility of repeated administration free from the risks associated with other types of magnetic contrast agents.
CRIS-Team Scopus Importer:2024-03-08
Keywords: atherosclerosis; histology; macrophages; plaque vulnerability; rabbit model; SPION-enhanced MRI; tissue iron

Analysis of Process Costing for the Use of Navigation Systems in Functional Endoscopic Sinus Surgery - Schwan, Franziska Eva; Traxdorf, Maximilian; Seebauer, Caroline Theresa; Sekita, Alexander; Habekost, Cornelia; Iro, Heinrich; Bohr, Christopher (Applied Sciences, 2021)
Featured Application This paper and its findings are important for any clinic that is thinking about setting up a navigation system for its ENT department, concerning the costs, efficiency in the operating room, and applicability for training purposes. (1) Background: The use of navigation systems is rarely necessary for routine sinus surgery. They may prove to be advantageous for difficult operations, for example, in finding structures that are difficult to reach, in the treatment of cancers, or in revisional surgery. Navigation systems are also said to have positive effects on the self-confidence of surgeons in stressful situations and in the training of doctors. (2) Methods: This retrospective study included patients who underwent surgical treatment for chronic sinusitis from 2012 to 2016 at the ENT clinic of the University Hospital, Erlangen. Two groups were formed; one includes patients without navigated sinus surgery, the other includes those with navigation. The incision-suture times of both groups and cost analysis are compared. An appropriate cost estimate for sinus surgery is determined. (3) Results: From the available results, no economically efficient navigation systems in sinus surgery at the ENT clinic can be shown. The main reason is that lengthening the operating time leads to higher costs. (4) Conclusions: Although the use of a navigation system for endonasal sinus surgery cannot be economically justified, it is an important tool, especially in cases with complex anatomical conditions, and the system is essential for training purposes.
CRIS-Team WoS Importer:2021-10-08

Cerebral lesions in the central pain matrix are associated with headache in multiple sclerosis - Fröhlich, Kilian; Macha, Kosmas; Siedler, Gabriela; Sekita, Alexander; Haupenthal, David; Mrochen, Anne; Wang, Ruihao; Schembs, Leah; Dörfler, Arnd; Seifert, Frank; Schwab, Stefan; Winder, Klemens (Scientific Reports, 2025)
Headache is very frequent in multiple sclerosis. However, the question whether headache is just coincidental or may be secondary due to inflammatory cerebral multiple sclerosis lesions is yet to be clarified. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in patients with multiple sclerosis and comorbid headache using voxel-based lesion symptom mapping (VLSM). Patients with multiple sclerosis and headache were prospectively identified and included in a university neurological center between 2017 and 2023. Only patients with headache onset after first manifestation of multiple sclerosis were included. Demographic and clinical data were assessed, and lesion volumes calculated. Cerebral lesion sites were correlated voxel-wise with presence and absence of headache using non-parametric permutation testing. A cohort of multiple sclerosis patients served as controls for the VLSM-analysis. 48 multiple sclerosis patients with headache were included, as well as 92 controls without headache. Of the 48 patients with headache, 39 (81%) were female and nine (19%) were male. Mean age was significantly higher in headache patients than in controls (51 + / − 11 vs. 42 + / − 11 years, p < 0.05). EDSS, disease duration and lesion volumes did not significantly differ between both groups. Lesion overlap of all patients demonstrated a distribution of white matter lesions consistently in all subcortical brain areas. The VLSM-analysis showed associations between headache and lesion clusters in the left insula, left hippocampus and right thalamus. In our study, multiple sclerosis lesions in the left insula, left hippocampus and right thalamus were associated with headache in multiple sclerosis patients. The data therefore indicates that headache in multiple sclerosis may, in a proportion of patients, result from lesions in the central nervous systems’ pain processing network. Trial registration: No. 93_17 B, Ethics committee of the University Hospital Erlangen-Nürnberg.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cerebral lesions; Headache; Multiple sclerosis; Voxel-based lesion symptom mapping

Long-Term Survival, Burden of Disease, and Patient-Centered Outcomes in Maximally Treated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Sekita, Alexander; Balk, Stefanie; Haupenthal, David; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Macha, Kosmas; Schwab, Stefan; Kuramatsu, Joji; Sembill, Jochen (Annals of Clinical and Translational Neurology, 2025)
Objective: Increasing evidence shows that patients with intracerebral hemorrhage (ICH) can achieve better-than-expected outcomes with aggressive therapy. However, real-world long-term data, patient-centered outcomes, and societal measures after maximal ICH treatment are lacking. This study aimed to analyze 5-year survival, utility-weighted functional outcomes, and burden of disease in maximally treated ICH patients, stratified by max-ICH Score. Methods: This study investigated consecutive patients with spontaneous ICH included in the single-center Longitudinal Cohort Study on ICH Care (UKER-ICH, NCT03183167, 2006–2015). We included all patients without early care limitations, hereinafter referred to as maximally treated. We analyzed the stratification by max-ICH Score of cumulative 5-year survival using Kaplan–Meier estimates and COX regression modeling, disease burden using disability-adjusted life years (DALYs), and patient-centered outcome at 12 months using the Utility-Weighted modified Rankin Scale (UW-mRS). Results: The 5-year survival rate of the included 1022 maximally treated patients was 53%, stratified by max-ICH Score (0 points: 85%, 1: 91%, 2: 69%, 3: 59%, 4: 47%, 5: 32%, 6: 29%, 7: 18%, ≥ 8: 0%, log-rank p < 0.001). The mean number of DALYs was 8.94 (±8.15, standard deviation [SD]), consisting of 4.27 years of life lost (±7.79, SD) and 4.67 years lived with disability (±6.38, SD). Patients with a max-ICH Score of 5 had the highest burden of disease (12.76 [±9.43, SD]). The mean UW-mRS at 12 months was 0.45 (±0.37, SD) and decreased with increasing max-ICH Score (0: 0.80 [±0.23], 1: 0.73 [±0.29], 2: 0.67 [±0.29], 3: 0.50 [±0.34], 4: 0.39 [±0.34], 5: 0.25 [±0.30], 6: 0.19 [±0.28], 7: 0.16 [±0.26], ≥ 8: 0.08 [±0.22], p < 0.001). Interpretation: These observational data, stratified by max-ICH Score, provide patients and treating physicians with an initial severity assessment in terms of potential long-term patient-centered outcomes and burden of disease following maximal treatment.
CRIS-Team Scopus Importer:2025-04-25
Keywords: intracerebral hemorrhage prognosis; patient-centered outcomes; stroke disability burden